mTOR pathway mediates the endoplasmic reticulum stress -apoptosis of CD4+ T cell through inhibiting autophagy flux in sepsis - Xianli Lei; Guoyu Zhao; Yawen Xie; Na Cui (Inflammation Research, 2026)
Background CD4 + T cells are major reactive subpopulation for cellular and humoral immune responses following sepsis. The apoptosis of CD4 + T cells may contribute to sepsis-induced immunosuppression, and preventing the induction of endoplasmic reticulum stress (ERS) can ameliorate apoptosis of CD4 + T cells in sepsis. The mechanistic target of rapamycin (mTOR) pathway performs an essential regulatory role on ERS-apoptosis of CD4 + T cells. This study aims to elucidate the underlying mechanisms of mTOR regulation of ERS-apoptosis of CD4 + T cells. Methods In this study, based on the cecal ligation and puncture (CLP) model, 4-phenylbutyric acid (4-PBA), we firstly detected the percentage of ERS-apoptosis of CD4 + T cells with flow cytometry, Western blotting. Next, we observed the autophagy process and related makers with transmission electron microscopy (TEM) and Western blotting. Furthermore, we created CLP models with T cell-specific mTOR and TSC1 genetic knockout mice, and bafilomycin A1(Baf-A1), a selective inhibitor of autophagy to explore the regulatory role and underlying mechanism of mTOR on ERS-apoptosis of CD4 + T cells. With rapamycin, we proved the clinical potential of mTOR. Results Here we observed a considerably higher percentage of apoptotic CD4 + T cells in sepsis, and 4-PBA (an inhibitor of ERS) could alleviate not only ERS, but also the apoptosis of CD4 + T cells. As our previous work proved, deletion of mTOR decreased ERS-apoptosis of CD4 + T cells in sepsis. Furthermore, deficient autophagy, especially impaired autophagic flux was observed in sepsis. Mechanistically, we found knockdown of mTOR erased impaired autophagic flux, decreased ER stress-induced apoptosis, which could be reversed by Baf-A1. More importantly, rapamycin (inhibitor of mTOR) showed great clinical potential. Conclusion we proved that mTOR deletion could alleviate CD4 + T cells ERS-apoptosis by rescuing autophagy involving autophagosome –lysosome fusion. For the first time, we demonstrate the mTOR-autophagy-ERS-apoptosis axis in sepsis, enriching the targets for future discovery of new sepsis therapies.